Penyuluhan Kesehatan tentang Cuci Tangan di SDN 11 Tanjung Gunung Bangka Tengah - leni, marleni; Megawati, Megawati; Marleni, Marleni (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Hand washing is the process of mechanically removing dirt and dust from the skin of the hands using soap and water. Hands are the main vector for the spread of germs that cause disease. Due to a lack of hand washing habits, children are at high risk of developing diarrhea and respiratory diseases which often lead to death. Children at school are the best candidates to apply PHBS values ??and have the capacity to act as agents of change, promoting PHBS at home, school and community. The method for implementing hand washing education is by introducing hand washing material to the public. Participants in this outreach activity are students and accompanying teachers. The stages in hand washing education include the problem identification stage, the counseling stage, and the evaluation stage. Data obtained from interviews with the SDN 11 Tanjung Gunung school, it was found that students at the school had not been given knowledge about proper hand washing hygiene so they could not wash their hands properly. So it is necessary to provide education about the 6 steps for washing hands with soap and direct practice on how to wash hands correctly. Based on the results and discussion that have been explained, it can be concluded that the level of understanding of students in understanding and practicing the 6 steps for washing hands as determined by WHO is quite effective and has increased after the counseling was carried out.